2001
DOI: 10.2307/2679984
|View full text |Cite
|
Sign up to set email alerts
|

Population Persistence in Rivers and Estuaries

Abstract: A wide variety of organisms inhabit streams, rivers, and estuaries where they are continually subjected to downstream drift. It is well known that when this is the only transport process, extinction is inevitable (the ''drift paradox''). Using a series of analytical and numerical models, representing a range of hydrodynamic scenarios, we demonstrate that the action of diffusive dispersal can permit persistence in an advective environment. The mechanism underlying this phenomenon is that diffusive dispersal can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
239
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(244 citation statements)
references
References 23 publications
(34 reference statements)
5
239
0
Order By: Relevance
“…But how does one explain the persistence of the many species that are commonly found to drift but do not have an aerial adult stage (Humphries and Ruxton 2002)? Speirs and Gurney (2001) and Humphries and Ruxton (2002) demonstrated that long-distance flight by aerial adults is not required to prevent extinction of upstream reaches. It can be achieved by very small upstream movements of individuals along the substrate.…”
Section: Discussionmentioning
confidence: 97%
“…But how does one explain the persistence of the many species that are commonly found to drift but do not have an aerial adult stage (Humphries and Ruxton 2002)? Speirs and Gurney (2001) and Humphries and Ruxton (2002) demonstrated that long-distance flight by aerial adults is not required to prevent extinction of upstream reaches. It can be achieved by very small upstream movements of individuals along the substrate.…”
Section: Discussionmentioning
confidence: 97%
“…The downstream movement of microfauna in Australia has not been investigated but has been recorded from many other systems. Drift is a characteristic of many invertebrate taxa and allows animals to recolonise newly inundated slackwaters following periods of high flows (Speirs & Gurney, 2001). Studies of microfaunal drift have suggested that animals found regularly in the drift are not likely to be benthic in origin (Campbell, 2002) but may be derived from the plankton of still water zones along the river edge (Braioni, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Recent modeling efforts for the drift paradox identified a "critical flow speed" below which a population can persist on a long enough stretch of a river and also spread upstream in form of a moving front (Speirs and Gurney, 2001;Lutscher et al, 2005;Pachepsky et al, 2005). These models neglect spatial heterogeneities and assume a homogeneous habitat.…”
Section: Introductionmentioning
confidence: 99%